2001
DOI: 10.1007/s002510100339
|View full text |Cite
|
Sign up to set email alerts
|

Structural organization of the human MS4A gene cluster on Chromosome 11q12

Abstract: CD20, the high-affinity IgE receptor beta chain (FcepsilonRIbeta), and HTm4 are structurally related cell surface proteins expressed by hematopoietic cells. Recently, 16 novel human and mouse genes were identified that encode new members of this nascent protein family that we have named the membrane-spanning 4A gene family, with at least 12 subgroups (MS4A1-MS4A12). In the current study, we identified three additional human MS4A genes: MS4A4E, MS4A6E, and MS4A10. All family members have at least four potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
85
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 51 publications
1
85
0
Order By: Relevance
“…Topologically, this structure provides two tails that are available for protein-protein interactions (2). HTm4 localizes to the nuclear membrane.…”
Section: Mechanism For Htm4-induced Dissociation Of Cyclin a Frommentioning
confidence: 99%
See 1 more Smart Citation
“…Topologically, this structure provides two tails that are available for protein-protein interactions (2). HTm4 localizes to the nuclear membrane.…”
Section: Mechanism For Htm4-induced Dissociation Of Cyclin a Frommentioning
confidence: 99%
“…However, a diverse functionality is beginning to emerge. These functions include roles such as cell surface signaling receptors and intracellular adapter proteins (1)(2)(3)(4)(5)22).…”
mentioning
confidence: 99%
“…The precise function of CD20 is unknown and it has been reported to act as an ion channel expressed in the plasma membrane of normal and malignant B cells. Liang et al have reported that CD20 may operate as a calcium storage channel facilitating entry of intracellular calcium following BCR-induced emptying of intracellular calcium (4). The importance of CD20 as a target for mAb immunotherapy is irrefutable, and anti-CD20 monoclonal antibodies appear to be ideal for B-cell diseases.…”
Section: Introductionmentioning
confidence: 99%
“…It spans the plasma membrane four times and both C-and N-termini are contained within the cell (3)(4)(5)(6). The precise function of CD20 is unknown and it has been reported to act as an ion channel expressed in the plasma membrane of normal and malignant B cells.…”
Section: Introductionmentioning
confidence: 99%
“…7 CD20, which contains both an N and C terminus within the cell, is a member of the MS4A protein group. [8][9][10] CD20 is comprised of two extracellular loops, of which the larger component is made up of 44 amino acids. Rituximab was the first mouse-human chimeric antibody clinically developed to target CD20 and acts through multiple different mechanisms, including complement-mediated cytotoxicity (CDC), antibody-dependent cytotoxicity (ADCC), and direct toxicity.…”
Section: Rituximab and Targeting Of Cd20mentioning
confidence: 99%